SINERGI STRATEGIS: MENGOPTIMALKAN KOLABORASI SEKOLAH DAN MASYARAKAT DALAM PENGUATAN EKOSISTEM PENDIDIKAN YANG BERMUTU - Hanafi, Mutia Safitri Roy; Simbolon, Ali Mustopa Yakub; Eriya, Vifri; Nawawi, Rayhan; Nurazani, Adilah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2025)
Education cannot run optimally without the active support of the community. Schools, as formal educational institutions, hold the responsibility to nurture knowledgeable and well-behaved students, yet their success largely depends on effective collaboration with society. The relationship between schools and the community reflects a communicative, participatory, and mutually beneficial partnership. Through this collaboration, schools receive moral, material, and participatory support from the community, while society benefits from improved educational quality and social empowerment. The findings indicate that transparency, active participation, and democratic leadership are key factors in establishing effective and sustainable partnerships to enhance the quality of education